Voorlopige kriteria vir wie en wat die leksikograaf is - Swart, Marius; du Plessis, André H. (Lexikos, 2023)
Proposed Criteria for Being a Lexicographer. There is surprisingly little systematic academic research on who exactly lexicographers are. This issue was identified a decade ago by Rufus Gouws. Gouws (2012) not only investigates the activities of those involved in Lexicography, but critically questions the roles of the active participants. Gouws (ibid.) concludes by emphasising that it is imperative to develop unambiguous criteria for who can be called a lexicographer. This article aims to help develop these criteria by placing the work of Gouws under the microscope in the form of a case study with an underlying thematic analysis. Gouws' own contributions to the meta- and practical lexicography, as well as to dictionary didactics and pedagogy, attests to his productivity, expertise and relevance. This case study includes a literature review of Gouws' research articles from the last 10 years since the publication of the 2012 article mentioned above. The articles are analysed thematically to deduce the general roles and activities of the lexicographer. These roles or activities are discussed incisively, and from this discussion, a set of tentative criteria is proposed for who can be called a lexicographer.Keywords: lexicographer, metalexicographer, dictionary maker, educator, linguist, linguistic citizenship, activism